An investigation of dynamic behavior of the cylindrical shells under thermal effect. (September 2018) - Hamzah, Adawiya Ali; Jobair, Hussein K.; Abdullah, Oday I.; Hashim, Emad Talib; Sabri, Laith A.
Abstract: Study the vibration characteristics of the cylindrical shell is considered a very important issue, because of the cylindrical shells are used for different applications in engineering fields such as missiles, electric motors, rocketry, etc. In different applications, the cylindrical shells have produced a high level of noise and vibration that effect on the behavior and performance of the systems. In some cases, when those systems work under these conditions for enough time, this will lead the systems to failure or at least change the situation of those systems from stable zone to unstable zone. In this paper, the finite element method was used to investigate deeply the vibration characteristics of cylindrical shells under different surrounding temperatures. Furthermore, the effect of thickness on the dynamic characteristics was investigated.